Gastroesophageal Reflux: Are There Differences of Characteristic in Infants and Children - Badriul Hegar; Anita Juniatiningsih (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2008)
Background: Gastroesophageal reflux (GER) is an involuntary passage of gastric contents into the esophagus. GER in infancy is usually a physiologic reflux whereas GER in children more than 12 months old is often considered as a pathologic reflux although without any clinical complications. This consideration may lead over-treatment of GER in children. The objective of this study was to find out the difference of GER characteristic in ‘healthy’ infants and children. Method: Cross sectional study in children age 0-36 months at Cipto Mangunkusumo Hospital Jakarta during 2005-2007 with inclusion criteria: clinically healthy, regurgitations/vomits ³ 4 times/day, well nourished and other etiologies of vomiting had been excluded. The characteristic of GER was evaluated by esophageal pH monitoring (pH-metri) included number of reflux episodes, reflux duration 5 minutes, and reflux index. Results: Sixty children were enrolled in the study; consisting 30 infants (age 0-12 months) and 30 children (age 13-36 months). The median number of reflux in infants was 18 ( range1-19), whereas the median in children was 17 (range 3-27) ( p = 0.47). The median number of reflux 5 minutes was 2 (range 0-2), whereas the median in children was 3 (0-30) (p = 0.85). The median reflux index in infants was 4.5% (range 0.6%-22.9%) whereas the median in children was 6.35% (0.1%-87.%) (p = 0.34). Conclusion: The characteristic of GER in ‘healthy’ infants and children were not significantly different; however reflux index 5% (pathologic GER) was seen in children age 13-36 months. Clinical course monitoring are important in infants and children with GER. Keywords: gastroesophageal reflux, regurgitation, infant, children, pH monitoring